Відображення любові до землі як ментальної риси українців у східностеповому говірковому тексті - Дворянкін, В. О. (Центральноукраїнський державний університет імені Володимира Винниченка, 2024)
У статті розглянуто особливості мовних ресурсів для вираження любові до землі як ментальної риси українців на матеріалі діалектного монологічного тексту-спогаду, зафіксованого 2012 року в східностеповій говірці села Красноармійське Новоазовського району Донецької області (нині – село Хрещатицьке Новоазовської міської громади Кальміуського району Донецької області (окуповане з 2014 року)) від мешканця (пенсіонера) Гамалія Миколи Андрійовича, 1949 року народження, освіта – 8 класів. Мета розвідки – опис вербальних засобів для вираження любові до землі як риси української ментальності на зазначеному вище матеріалі. Джерелом студії стала віртуальна фонотека мовлення конкретного говірконосія. Любов до землі як один із сегментів українського менталітету в поданому фрагменті східностепового дискурсу відображена як любов до городництва. Вирощування рослинницької сільськогосподарської продукції (овочевих культур) є копіткою справою, яка потребує значних зусиль у певних кліматичних умовах, зокрема в засушливому східностеповому регіоні. Виділено такі вербальні засоби вираження любові до землі як ментальної риси українців: номінації овочевих культур як складник сільськогосподарської лексики; речення з дієслівними формами лʼуб| лʼу занʼі| матисʼ, занʼі| майусʼ разом із субстантивованим займенником цим та прислівником даў| но, які безпосередньо сигналізують про потяг до улюбленої справи; повтори; речення; дієслівні форми; дієслівно-іменні словосполучення; різні конструкції тощо.

The article is concerned with peculiarities of lingual resources meant to express love for the land as the mental feature of the Ukrainians. On the basis of a dialect text-memoir monologue spotted in 2012 as the eastern steppe dialect in the village of Krasnoarmiiske of Novoazovsk Rural Area in Donetsk Region (nowadays the village of Khreshchatytske of Novoazovsk Community in Kalmius Rural Area of Donetsk Region (seized by the Russians in 2014)) from Hamalii Mykola born in 1949, a local resident (pensioner) whose education is 8 years of study at secondary school. Vitality of the present research does not lie in the insufficient state of study of the newly built Ukrainian dialect areal of the south of Donetsk Region alone. Vitality of the present research also lies in the need to preserve the national dialect archive under the conditions of Russia/Ukraine war that caused forced migration and significant reduction in the number of dialect speakers, in particular in the number of indigenous residents of Russia-occupied populated areas. The goal of the research is to describe lingual means meant to express love for the land as the feature of Ukrainian mentality on the basis of the aforementioned material. The following assignments made it possible to reach the goal: to spot the dialectal material; to record the dialectal discourse with the help of phonetic transcription; to define lingual means aimed at representation of love for the land as one of the elements of Ukrainian mentality. A particular dialect speaker’s virtual speaking phonetics became the source of the research. In the presented fragment of the eastern steppe discourse, love for the land as a segment of Ukrainian mentality reveals itself as love for gardening. Growing agricultural crops (vegetable crops) is a hard spadework that needs great effort under certain climatic conditions, in particular in the droughty eastern steppe region. The research found such lingual means of expressing love for the land, the mental feature of the Ukrainians, as nomination of vegetable crops as a component of agricultural lexis; sentences containing verbal forms l’ub| l’u zan’i| matys’ (лʼуб| лʼу занʼі| матисʼ) and zan’i| maius’ (занʼі| майусʼ) along with the substantivized pronoun tsym (цим) and the adverb dav| no (даў| но), all this directly signaling about passion for what people are fond of doing; repetitions; sentences; verbal forms; verbalnominal word combinations; various constructions, etc. We can see the prospects of the research studios as the opportunity to further study archival records of dialectal speaking typical of representatives of the eastern steppe dialect landscape (unfortunately, it is impossible to go on spotting oral dialect speaking now due to the warfare and seizure of a part of Donetsk Region). Further dialectological regional research will promote comprehensive lingual portrayal of each Ukrainian region, in particular Donetsk Region.
Reflection of love for the land as the mental feature of the ukrainians in the eastern steppe dialect text
Keywords: українські східностепові говірки; віртуальна фонотека; діалектний монологічний текст-спогад; любов до землі; ментальна риса українців; сільськогосподарська лексика; номінації овочевих культур; Ukrainian eastern steppe dialects; virtual phonetic archive; dialect text-memoir monologue; love for the land; agricultural lexis; mental feature of the Ukrainians; nomination of vegetable crops